'A Single Purpose: The Conquest of the Foreign Art Markets': Theatre and Cultural Diplomacy in Mussolini's Italy (1919–1927). (August 2022) - Paoletti, Matteo
Abstract : This article explores the role of theatre in the strategies of cultural diplomacy that developed in Italy between the last years of the liberal state (1919–22) and the rise of Benito Mussolini. It covers the period until 1927, when the establishment of the Istituti Italiani di Cultura (Italian Cultural Institutes) and the approval of a new regulatory framework for migration marked a new era for fascist soft-power ambitions. The article draws upon unpublished sources of the Historical Diplomatic Archive of the Italian Ministry of Foreign Affairs and offers a new perspective on the use of theatre and the performing arts as a tool for cultural diplomacy through the testimony of such flagship authors as Luigi Pirandello, Filippo Tommaso Marinetti, Alfredo Casella, and Pietro Mascagni. Matteo Paoletti is a Senior Assistant Professor in Theatre Studies at the University of Bologna and part of the research project 'Historia y patrimonio de la Argentina moderna' with the Universidad Nacional de San Martín, Buenos Aires. He was a Cultural Attaché at the Italian Ministry of Foreign Affairs, and oversaw the 2003 Convention on Intangible Cultural Heritage for the Italian National Commission for UNESCO. His recent publications include 'A Huge Revolution of Theatrical Commerce' : Walter Mocchi and the Italian Musical Theatre Business in South America (Cambridge University Press, 2020)